Influences in Ethical Dilemmas of Increasing Intensity - Mc Devitt, Roselie (Journal of business ethics, 2002)
This study attempts to extend the literature in ethics research by developing and testing a model of an individual's ethical system which identifies the sources of influence on the decision process. The model is developed from an interdisciplinary literature review and includes six subsystems or spheres that exert influence on an individual: the workplace, family, religion, legal system, community, and profession. The study also examines the role of materiality in the decision-making process., Using this model, empirical tests identify the spheres that exert the most influence on the decision-maker facing an ethical dilemma. In addition, the relative importance of the spheres and the interaction among the spheres is examined. Findings show that: (1) individuals rate variables at different levels of importance as the materiality of the breach changes and (2) the spheres that are considered most important for minor ethical breaches are different than the spheres considered most influential in a major ethical situation., Exploratory factor analysis suggests that the variables representing the spheres can be summarized by three factors. Further, it indicates that these factors change with materiality.